Multidimensional poverty index: a multilevel analysis of deprivation among Iranian older adults - Mohaqeqi Kamal, SH; Basakha, M; Alkire, S (Cambridge University Press, 2022)
Although the older adult population faces a higher risk of poverty compared to others, there is no clear picture of their poverty in Iran. The aim of this study was to measure multidimensional poverty and its related factors among Iranian older adults. This cross-sectional study was conducted from July to November 2019 and collected data by interviewing 1,280 participants in Tehran, Iran. To compute multidimensional poverty, four dimensions were used: health (disabilities), education, housing and standard of living. Single and multidimensional poverty and the joint distribution of deprivation were calculated. Multilevel logistic regression models were used to determine the relationship between predictor variables and outcome (multidimensional poverty). Multidimensional poverty among Tehran’s older people was 59.0 per cent. The prevalence of health, housing, education and standard of living deprivations were 15.4, 25.3, 29.5 and 29.9 per cent, respectively. Furthermore, multivariate analysis shows that living with a spouse, being employed, and having health and social insurance coverage were protective factors, while being female was a risk factor for multidimensional poverty. Approximately 21 per cent of multidimensional poverty variance was attributed to the district level and the remaining was assigned to individual-level factors. This study showed that the older adults living in different areas of Tehran experience different aspects of poverty. So paying attention to the dimensions of multidimensional poverty can play an important role in customising the policies of each district. Also, the findings of this study on risk and protective factors of multidimensional poverty can be effective in designing and implementing interventions to mitigate poverty among the older adults.